Colonial mestizaje and its consequences for human capital and early twentieth century regional industrialization in Colombia (2012)
This paper quantitatively shows that the 1945 regional differences in the degree of development of manufacturing industry are explained by human capital accumulation prior to industrial development. Human capital accumulation was more intense in the regions with higher presence of non white free population - the "Free of all Colors" caste - at the end of the colonial times. Once the country began industrializing at the beginning of the twentieth century the former "Free of all Colors" regions were better prepared to adapt and to use the industrial technology and hence manufacturing industry rose with greater strength in those regions.